Complementary anion binding by bidentate boron-containing Lewis acids - Coombs, N; Aldridge, S; Wiltshire, G; Kays, D; Bresner, C; Ooi, L (2005)
Anion binding by the pyroborates (catB)2O (1, cat = O 2C6H4-1,2) and (S,S-Ph2C 2H2O2B)2O (2) has been investigated by spectroscopic, structural and titration methods. 1 has been shown to act as a bifunctional Lewis acid, exemplified by the complementary (1:1) binding of bidentate bases such as acetate and dihydrogen phosphate. The former complex has been characterized in the solid state by X-ray diffraction and a binding constant of 1500 ± 550 M-1 determined in chloroform solution. The reaction of 2 with acetate, by contrast, leads to breakdown of the Lewis acid chelate and to the formation of the homochiral borate anion [(S,S-Ph 2C2H2O2)2B]- in good yield (84% based on the chiral component). © 2005 Elsevier B.V. All rights reserved.